2020
DOI: 10.1002/jum.15527
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Deep Learning Network to Classify Inferior Vena Cava Collapse to Predict Fluid Responsiveness

Abstract: Objectives-To create a deep learning algorithm capable of video classification, using a long short-term memory (LSTM) network, to analyze collapsibility of the inferior vena cava (IVC) to predict fluid responsiveness in critically ill patients.Methods-We used a data set of IVC ultrasound (US) videos to train the LSTM network. The data set was created from IVC US videos of spontaneously breathing critically ill patients undergoing intravenous fluid resuscitation as part of 2 prior prospective studies. We random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…After the full-text review, 62 articles were excluded due to insufficient data ( n = 36), lack of 2-by-2 data ( n = 25), and not being original ( n = 1). Finally, 30 studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] comprising 1719 patients were included in this review ( Figure 1 ); detailed information about the eligible studies is shown in Table 1 . In cases of the IJV [ 29 , 36 , 42 ], FV (was not detected), and SCV [ 41 ], we were not able to conduct the meta-analysis due to an insufficient number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the full-text review, 62 articles were excluded due to insufficient data ( n = 36), lack of 2-by-2 data ( n = 25), and not being original ( n = 1). Finally, 30 studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] comprising 1719 patients were included in this review ( Figure 1 ); detailed information about the eligible studies is shown in Table 1 . In cases of the IJV [ 29 , 36 , 42 ], FV (was not detected), and SCV [ 41 ], we were not able to conduct the meta-analysis due to an insufficient number of studies.…”
Section: Resultsmentioning
confidence: 99%
“…We extracted the results of experts because other studies were conducted by experts. One study by Blavius [ 50 ] was a comparative study between artificial intelligence and human. We extracted the result of the training dataset by humans because the number of test datasets was much smaller than the test set (20 vs. 175).…”
Section: Resultsmentioning
confidence: 99%
“…They used a public dataset with 750,018 individual ultrasound images of five different types and showed that the classification accuracy varied from 96% to 85.6% for the various models, with VGG-16 giving the best performance while the DenseNet201 performed the worst for classification. Another work by Blaivas et al [ 103 ] proposed a LSTM network for inferior vena cava (IVC) POCUS videos in patients undergoing the intravenous fluid resuscitation and use 211 videos and achieved the receiver operating characteristic curve of 0.70 (95% confidence interval [CI], 0.43–1.00) for predicting the fluid responsiveness. Generative Adversarial Networks (GANS) have also gained popularity for generating more data as well as applicable in the cases where the paired input/output pairs are not easily available for training the models.…”
Section: Advanced Us Imaging In Cardiology and DL Techniquesmentioning
confidence: 99%
“…In a third study, Blaivas et al created a DL algorithm to analyze collapsibility of the inferior vena cava to predict fluid responsiveness in critically ill patients. The DL algorithm predicted fluid responsiveness with an AUC of 0.70, compared to an AUC of 0.94 by two POCUS experts using video review and manual caliper measurements [ 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…DL has also been applied to help make more advanced diagnoses including heart failure with preserved ejection fraction, cardiomyopathy, amyloidosis, and pulmonary hypertension [20][21][22][23][24]. [27].…”
Section: Figure 1: the Framework Of Deep Learning Machine Learning And Artificial Intelligence Figure 2: Diagram Showing Neural Network Tmentioning
confidence: 99%